Pengembangan Format Dokumentasi Asuhan Keperawatan Gawat Darurat Berbasis SDKI, SLKI, dan SIKI - Nelly Hermala Dewi; Eti Suryati; Fertin Mulyanasari; Lisnawati Yupartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the development of the emergency nursing care documentation format based on the IDHS, SLKI, and SIKI, the quality of the format development, and the quality of the documentation for the development of the design in the Emergency Room of Dradjat Prawiranegara Hospital Serang Banten. The research method is Research and Development. The result of this research is that the nursing diagnosis is determined according to the primary assessment. The quality of developing the emergency nursing care documentation format is functional, efficient, and usable. And the quality of emergency nursing care documentation includes completeness, accuracy, relevance, and good novelty. In conclusion, the format of nursing care documentation based on IDHS, SLKI, SIKI can be used in the emergency room to improve the quality of nursing care. Keywords: Documentation of Emergency Nursing Care, IDHS, SLKI, SIKI